Structural Insights on the Role of Antibodies in HIV-1 Vaccine and Therapy - West, Anthony P. (2014)
Despite 30 years of effort, there is no effective vaccine for HIV-1. However, antibodies can prevent HIV-1 infection in humanized mice and macaques when passively transferred. New single-cell-based methods have uncovered many broad and potent donor-derived antibodies, and structural studies have revealed the molecular bases for their activities. The new data suggest why such antibodies are difficult to elicit and inform HIV-1 vaccine development efforts. In addition to protecting against infection, the newly identified antibodies can suppress active infections in mice and macaques, suggesting they could be valuable additions to anti-HIV-1 therapies and to strategies to eradicate HIV-1 infection.